Clinical frailty independently predicts early mortality after ischaemic stroke - Romero-Ortuno, Roman (My University, 2020)
Background: Clinical frailty is an important syndrome for clinical care and research, independently predicting mortality and rates of institutionalisation in a range of medical conditions. However, there has been little research into the role of frailty in stroke. Objective: This study investigates the effect of frailty on 28-day mortality following ischaemic stroke and outcomes following stroke thrombolysis. Methods: Frailty was measured using the Clinical Frailty Scale (CFS) for all ischaemic stroke admissions aged ≥75 years. Stroke severity was measured using the National Institutes of Health Stroke Scale (NIHSS). 28-day mortality and clinical outcomes were collected retrospectively. Analysis included both dichotomised measures of frailty (non-frail: CFS 1-4, frail: 5-8) and CFS as a continuous ordinal scale. Results: In 433 individuals with ischaemic stroke, 28-day mortality was higher in frail versus non-frail individuals (39 (16.7%) versus 10 (5%), P < 0.01). On multivariable analysis, a one-point increase in CFS was independently associated with 28-day mortality (OR 1.03 (1.01-1.05)). In 63 thrombolysed individuals, median NIHSS reduced significantly in non-frail individuals (12.5 (interquartile range (IQR) 9.25) to 5 (IQR 10.5), P < 0.01) but not in frail individuals (15 (IQR 11.5) to 16 (IQR 16.5), P = 0.23). On multivariable analysis, a one-point increase in CFS was independently associated with a one-point reduction in post-thrombolysis NIHSS improvement (coefficient 1.07, P = 0.03). Conclusion: Clinical frailty is independently associated with 28-day mortality after ischaemic stroke and appears independently associated with attenuated improvement in NIHSS following stroke thrombolysis. Further research is needed to elucidate the underlying mechanisms and how frailty may be utilised in clinical decision-making.
PUBLISHED
Keywords: post-thrombolysis NIHSS improvement; Clinical frailty; stroke; Frailty; Mortality; Thrombolysis; Older people; Ageing